Comparison of transient electromagnetic fields excited by single- and double-line grounded-wire sources on land. Issue 3 (28th January 2022) - Zhou, Nan-nan; Xue, Guoqiang; Li, Hai; Kangxin, Lei; Chen, Wen
SUMMARY: The lack of a systematic comparison of field surveys on land makes it challenging to select a suitable grounded-wire transient electromagnetic (TEM) source. Therefore, in this study, we compare land-based TEM methods with single- and double-line grounded-wire sources in the broadside direction. The comparison results indicate that the amplitude of the electric field from the double-line source is one or two orders weaker than that of the single-line source in the same time range. Further, we compare the detectability of horizontal electric fields for resistive or conductive targets by analysing the root mean square misfit and decay curves. According to the decay curve analysis, the double-line source shows better detectability for resistive targets, whereas the single-line source has a larger depth of investigation in the broadside direction. In the presence of a resistive target, sign reversal is more likely in the broadside direction for the double-line source than for the single-line source. In the field survey over Kalatongke Ni-Cu sulphide deposits in Xinjiang, China, both single- and double-line configurations can locate the resistive target; however, the latter configuration outperforms the former in discriminating the different values of the resistive rocks in the broadside direction. The double-line source will be the preferred choice for exploring resistive targets in the broadside direction.